Excretion of β-Lactam Antibiotics in Sweat—a Neglected Mechanism for Development of Antibiotic Resistance? - Høiby, Niels (American Society for Microbiology, 2000)
The concentrations of β-lactam antibiotics after standard doses were measured in blood and apocrine (axilla) and eccrine (forearm) sweat from six adult healthy persons. All persons had ceftazidime (axilla, 28.4 μg/ml; forearm, 11 μg/ml) and ceftriaxone (axilla, 8.9 μg/ml; forearm, 2.5 μg/ml) in sweat, and one person had cefuroxime in sweat (axilla, 7.8 μg/ml) (all data are mean peaks). Three persons had benzylpenicillin (axilla, 2.6 to 0.1 μg/ml) and one had phenoxymethylpenicillin (axilla, 0.4 μg/ml) in sweat. Excretion of β-lactam antibiotics in the sweat may explain why staphylococci so rapidly become resistant to these drugs.